Bibliometric Analysis of Multi Representation Based on Problem-Solving Skills Using VOSviewer - Erina Krisnaningsih; Maharani Ayu Nurdiana Putri; Tsabitamia Irba; Utama Alan Deta; Eko Hariyono; Nadi Suprapto (Berkala Ilmiah Pendidikan Fisika, 2021)
The purpose of this study was to analyze the scope related to the subject of problem-solving skills based on multiple representation in 2016 – 2020 with 20 documents through bibliometric analysis. The research method used was a literature study through all the articles analyzed in this study. The articles were taken from the Scopus database with sampling in 2003 – 2020, resulting in 29 scientific work data exported in *.ris (RIS) and *CVS formats. Then, those data were processed using VOSviewer and Microsoft Excel. The results of publications in the last five years have increased. Indonesia is the dominant country in publicizing papers about this topic. Institutions from Germany managed to publish most of the documents about multi representation. Meanwhile, Poland is the origin country of the authors with most publications. The visualization of research trends on multi representation resulted in four main clusters: (1) multi representation related to students, representation, and learning processes (2) multi representation as a class (3) multi representation related to the problem (4) multi representation as a model and process. Meanwhile, Indonesian researchers are very active in contributing to this topic, in line with the number of publications by country, namely Indonesia.